Hubungan Pengetahuan Petugas Laboratorium terhadap Penerapan Pemantapan Mutu Internal Pemeriksaan Glukosa Darah di RSUD Bahteramas Provinsi Sulawesi Tenggara - Hernawati Hernawati; Ni Ketut Ayu Mira Yanti; Putu Ayu Parwati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Laboratory staff knowledge is one of the key factors in ensuring the success of internal quality control in blood glucose testing. This study aims to determine the relationship between laboratory staff knowledge and the implementation of internal quality control at the Laboratory of RSUD Bahteramas, Southeast Sulawesi Province. This research used a quantitative approach with a correlational design. Data collection was carried out through questionnaires distributed to laboratory staff. Instrument testing was conducted through pilot testing, and data normality was assessed using the Shapiro-Wilk test. The relationship was analyzed using the Spearman correlation test. The results showed a significant relationship between staff knowledge and the implementation of internal quality control (p < 0.05). High knowledge contributed to more consistent and accurate application of quality procedures. These findings are supported by previous studies showing that staff knowledge competence positively correlates with the quality of laboratory services. This study is expected to serve as a basis for hospital management to improve technical training and supervision of laboratory staff.